Eastern European gas hub in European gas hubs system - Yaroshevych, Maryana (Human Geography Journal, 2018)
There are the questions considered in the article which have prospect of creation on the basis of the Ukrainian underground gas storages of the powerful East European gas regulator (hub) that will be capable to increase the level of energy security of Ukraine, liberalize domestic market of natural gas and to integrate into the European system of gas pipelines and to provide profitability of underground gas storages of the country. The development of the gas sector of Ukraine is a priority in the context of the implementation of Ukraine’s European integration plans in the economic sphere and is determined not only by the geographical location but also by the technological integration of the gas transportation infrastructure in the European economic space over the past decades. The entry of the Ukrainian natural gas market into the European gas market system will contribute to: enhancement of Ukraine’s energy security; improving the quality and level of relations between Ukraine and the EU countries in cooperation on the gas markets of Central and Eastern Europe; creating a favorable investment climate for the further development of the gas transmission system. Whereas the European experience, it can be argued that underground storages create a powerful base for the formation and further operation of the East European gas hub from a transport and logistics point of view.